Peran Perpustakaan Sekolah Dalam Mendukung Proses Pembelajaran Di Smpit Alfarisi Sleman DIY - Nurlita Khasiati (Balitbangda Provinsi Jambi, 2021)
The purpose of this research is to describe the role of the school library in supporting the learning process at SMPIT Salman Alfarisi Sleman DIY and to describe and know the library facilities at SMPIT Salman Alfarisi Sleman DIY. This research is descriptive research. Data collection techniques used in this research are through observation, interviews, and documentation study. The subjects of this research are library staff, school principals, teachers and students of SMPIT Salman Alfarisi Sleman DIY. The data analysis technique used descriptive data analysis, through the stages namely data collection, data condensation, data presentation, and drawing conclusions. The results showed that; (1) The library facilities of SMPIT Salman Alfarisi Sleman DIY are very narrow rooms, the storage places for the collections are not regular, the room lighting is also not bright, the library room also does not have air ventilation, adding to the library getting darker and infrastructure in the library, namely 2 large bookshelves, 2 small bookshelves, 5 reading chairs, 1 cupboard, 1 magazine rack, 1 desk and chair for library staff, (2) The role of school libraries in supporting the learning process at SMPIT Salman Alfarisi Sleman DIY, the supporting aspects are book collections , the 2013 curriculum book collection available is 44% of the total, loan services that are carried out openly, not computerized and student visits to the library every day are between 5-10 people, then one library staff is in charge of providing services and managing and book collection management is done by making put the inventory number, label it, stamp the school.